Parametric modelling of Malaysian teeth template using computer aided design - Ahmat, M. M.; Wahab, M. S.; Kassim, N. (Asian Research Publishing Network (ARPN), 2016)
This study explored a new method and process of design denture using CAD technology to develop a template of a complete denture. Computer aided design were used as a tool of the design process. Occlusion curve was set up as variable as to follow patient size. The maxilla and mandible teeth arrangement were treated as a template of Malaysian user. The accuracy of design is the main aspect of concern that match the patients' data so that the outcome product would be suitable with maximum comfort for the patient. The product of design template will be matched with the conventional method to compare the tolerance between both. The new design template helps to reduce the time consumption of conventional carving method. The final output of 3D geometry teeth templates design will represent the patient details.